HAK DAN KEWAJIBAN BURUH DALAM MENDAPATKAN KESEJAHTERAAN DI PT.PERSADA ALAM SUTERA SAMARINDA MENURUT UNDANG - UNDANG NOMOR 13 TAHUN 2003 - Ali Irham (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT This study entitled "Labor Rights and Obligation In Gaining Welfare At PT. Persada Alam Sutera Samarinda According to Law Number 13 Year 2003 ", under the guidance that I respect Ibu Ony Rosifany., SH., M. Hum as the Supervisor I and Erika Siluq., SH., M.Kn as Lecturer II Advisor, This Research Aims to describe and analyze labor welfare procedures in samarinda. To know and analyze the obstacle and supporting factors in Procedure to get labor welfare at company in samarinda Law Study Program, Faculty of Law, University of 17 August 1945 Samarinda.Based on the results of the research that the employment development is intended to provide employment and business field for each workforce so as to obtain employment and livelihoods that are suitable for humanity and as of Law No 13/2003From the research results can be concluded that labor is the main capital and the implementation of the development of community Pancasila, the most important goal of the community tujuajn is the welfare of the people including labor